Discrimination Perceptions of Turkish Skilled Migrants in Norway - Yilmaz Sener, Meltem (Border Crossing, 2022)
This study focuses on the discrimination perceptions of Turkish skilled migrants living in Norway. Based on semi-structured, in-depth interviews with 44 skilled migrants from Turkey, the paper discusses their perceptions of the following: i) prejudices against their ethnic group, ii) discrimination against themselves and other people from Turkey, and iii) the implications of prejudices and discrimination for how migrants from the same country perceive each other. Looking at the case of Turkish migrants in Norway, the paper argues that the prejudices against a certain migrant group lead to more polarization between different groups of migrants coming from the same country. When all the members of one ethnic group are marked and stereotyped, those who have enough capital (economic, social, cultural) use discursive and material strategies to distance themselves from an imagined migrant (of their ethnic origin) who is stereotyped.